INFLUENCE OF ENZYME PREPARATIONS ON MEAT PRODUCTIVITY IN YOUNG PIGS - Nadezhda V. Danilova; Anatoly Yu. Lavrentiev (Теория и практика переработки мяса)
It is found that when young growing pigs are fed with mixture of enzyme preparations of domestic manufacture, amilosubtilin G3x and cellolux-F, amilosubtilin G3x and protosubtilin G3x, for 150 days, the average live weight of pigs in experimental groups 1 and 2 increases by 13.1 kg and 5.3 kg, respectively, compared with control group. At the beginning of experiment, live weight of pigs ranged from 17.8 to 18.1 kg. In the end of experiment on day 150, the average live weight of pigs in control group (12 animals), experimental group 1 (12 animals), and experimental group 2 (12 animals) was 112.0 kg, 120.3 kg, and 125.1 kg, respectively. In two experimental groups, slaughter yield was 0.5% to 1.1% higher than in control group. Mean daily weight gain in control group, experimental group 1, and experimental group 2 was 628 g, 713 g, and 683 g, respectively. With minor differences in fat thickness, the lowest thickness was in animals from experimental group 1 (32.9 mm), while animals in control group and experimental group 2 had almost equal thickness of 33.6 mm. Higher values of live weight, slaughter yield and fat thickness have been obtained using a mixture of amilosubtilin G3x and cellolux-F. The annual economic benefit from the use of the studied enzyme supplements may range from 0.87 to 1.37 million rubles per 1,000 pigs.